2015
DOI: 10.1155/2015/602136
|View full text |Cite
|
Sign up to set email alerts
|

Storage Effect on Phenols and on the Antioxidant Activity of Extracts fromAnemopsis californicaand Inhibition of Elastase Enzyme

Abstract: The amount of total phenols and flavonoids and the antioxidant activity of leaf, stem, and rhizome methanolic extracts from a commonly consumedAnemopsis californicaunder different storage conditions were investigated. Storage conditions were at 50, 25, 4, and −20°C, protected or not from light, during 180 days. The inhibition of the elastase enzyme was also evaluated. The results demonstrated that leaf, stem, and rhizome methanolic extracts ofAnemopsis californicamaintain approximately up to 97 and 95% stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
15
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 29 publications
6
15
0
2
Order By: Relevance
“…In addition, a correlation between short storage period and high antioxidant capacity was observed. Several studies have reported on the effects of storage on antioxidant activity of plant extracts . Similarly to our results, the antioxidant activity of orange juice and shadblow serviceberry ( Amelanchier canadensis ) decreased during storage.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, a correlation between short storage period and high antioxidant capacity was observed. Several studies have reported on the effects of storage on antioxidant activity of plant extracts . Similarly to our results, the antioxidant activity of orange juice and shadblow serviceberry ( Amelanchier canadensis ) decreased during storage.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have reported on the effects of storage on antioxidant activity of plant extracts. [39][40][41][42][43] Similarly to our results, the antioxidant activity of orange juice 43 Figure 1B) suggesting their ability to scavenge superoxide anions and storage did not affect SOD activity. Similar observations, no significant changes in the activities of antioxidant enzymes such as SOD, were reported for erythrocytes extracts after storage at −80°C for 6, 12, and 21 months.…”
Section: Efficacy Of Thylakoids On Repairing Uv Exposure Damagesupporting
confidence: 86%
“…Del-Toro-Sánchez et al reported a massive 36% reduction in the TPC of the herb, Anemopsis californica , extracts stored at 50, 25 and 4 °C with exposure to light after 180 days. The authors reported that high temperature and light degraded the structure of the polyphenols [ 22 ]. Qu et al investigated the storage stability of phenolic compounds in sterilised liquid pomegranate peel extracts at 4 °C under light and dark conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The degradation of the compounds following extract storage that was observed in this study was consistent with previous findings [ 53 ], where the total phenolic content in Cornelian cherries extracts was found to decrease after being stored at 2 °C for up to 60 days. A drastic decrease was observed in the total phenolic and flavonoid content of Anemopsis californica extracts after being stored at 4 °C [ 54 ]. The decrease in total phenolics and flavonoids after prolonged storage was caused by various factors including oxidation by enzymes such as glycosidase, phenolase, and polyphenol oxidase (PPO), degradation of compounds, the polymerization of these compounds with proteins, and the conversion between free and bound phenolic substances [ 55 , 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%